Predicting insider espionage - a five-factor model - Danesy, Frank C. 1955- (Peter Lang, 2024)
Insider espionage has destabilized governments, jeopardized national security and critical infrastructures, diminished the economic strength of nations, and cost lives. Deterrence and detection — the two methods most used to combat this threat — often prove ineffective. The author, therefore, suggests placing more emphasis on prediction. This book is based on a four-year research project in which the author studied hundreds of cases of insider espionage in the government and private sectors across various countries. The project led to the development of the author’s Five-Factor Model of Insider Espionage, which he validated through multiple case analyses and a cross-case synthesis. This model aims to provide a framework to predict and thus mitigate the risks associated with insider espionage. The book will familiarize readers with the model and the underlying concepts.